The axonal cytoskeleton: from organization to function - Kevenaar, Josta T.; Hoogenraad, Casper C. (Frontiers in Molecular Neuroscience, 2015)
The axon is the single long fiber that extends from the neuron and transmits electrical signals away from the cell body. The neuronal cytoskeleton, composed of microtubules, actin filaments and neurofilaments, is not only required for axon formation and axonal transport but also provides the structural basis for several specialized axonal structures, such as the axon initial segment (AIS) and presynaptic boutons. Emerging evidence suggest that the unique cytoskeleton organization in the axon is essential for its structure and integrity. In addition, the increasing number of neurodevelopmental and neurodegenerative diseases linked to defect in actin- and microtubule-dependent processes emphasizes the importance of a properly regulated cytoskeleton for normal axonal functioning. Here, we provide an overview of the current understanding of actin and microtubule organization within the axon and discuss models for the functional role of the cytoskeleton at specialized axonal structures.